HRS: HPC-based automatic 3D building reconstruction system - Dingju Zhu; Jianping Fan (2008 International Conference on Audio, Language and Image Processing, 2008)
3D digital city is paid more and more attention on for they are expected to make life and business more convenient, but traditional 3D digital city are out of sync with reality for non-automatic 3D digital city reconstruction. Automatic 3D building reconstruction is vital for automatic 3D digital city reconstruction, for city mainly consists of buildings. Serial computing based automatic 3D building reconstruction from stereo-pair images and from single image studied recently still is too slow for synchronously updating 3D digital city. So we propose HRS (HPC-based automatic 3D building reconstruction system) to make use of HPC (high performance computing) to speed up automatic 3D building reconstruction.